2009
DOI: 10.1074/jbc.m109.009712
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Phage Display Antibodies Identify Distinct Epitopes with Complex Binding Characteristics

Abstract: Heparan sulfate (HS) binds and modulates the transport and activity of a large repertoire of regulatory proteins. The HS phage display antibodies are powerful tools for the analysis of native HS structure in situ; however, their epitopes are not well defined. Analysis of the binding specificities of a set of HS antibodies by competitive binding assays with well defined chemically modified heparins demonstrates that O-sulfates are essential for binding; however, increasing sulfation does not necessarily correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 68 publications
5
44
0
Order By: Relevance
“…However, it has recently been realised that binding may be more complex; individual antibodies recognising multiple HS structures. 16 This is consistent with the suggestion that a high degree of conformation- † 23 were both raised originally against bovine kidney HS and were selected for several reasons. They both recognised HS but by distinct epitopes, and their CDR-3 sequences, considered to be the major determinants of specificity, were very different, comprising SRKTRKPFMRK (6 basic residues out of 11) and HAPLRNTRTNT (2 basic residues plus histidine out of 11), respectively.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, it has recently been realised that binding may be more complex; individual antibodies recognising multiple HS structures. 16 This is consistent with the suggestion that a high degree of conformation- † 23 were both raised originally against bovine kidney HS and were selected for several reasons. They both recognised HS but by distinct epitopes, and their CDR-3 sequences, considered to be the major determinants of specificity, were very different, comprising SRKTRKPFMRK (6 basic residues out of 11) and HAPLRNTRTNT (2 basic residues plus histidine out of 11), respectively.…”
Section: Introductionsupporting
confidence: 70%
“…To examine the effects of cations on the binding of phage display antibodies to HS, a modification of an ELISA assay previously reported 16 was employed, in which the polysaccharides were first exposed to various cations before application of the phage display antibodies. Briefly, the polysaccharides were converted to the appropriate cation form by use of excess cation exchange resin (Dowex W-50) that had been converted from the acidic form to the appropriate cation form using a solution of the chloride of the metal ion concerned.…”
Section: Cations Alter the Binding Of Phage Display Antibodies To Hepmentioning
confidence: 99%
See 1 more Smart Citation
“…Verrecchio et al (24) reported that heparin-binding peptides were designed based on consensus sequences, (AKKARA) n and (ARKKAAKA) n (n ϭ 1-6), and then higher M r peptides 50 for inhibition of heparin-peptide binding was observed with 9 M heparin/HS, and chondroitin sulfate did not inhibit it. In addition, Schuksz et al (26) reported that the small molecule antagonist of heparan sulfate, surfen, bound to glycosaminoglycans, and the extent of binding increased according to charge density in the order heparin Ͼ dermatan sulfate Ͼ heparan sulfate Ͼ chondroitin sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…Because almost no glycosaminoglycans are immunoreactive and there are few antibodies against them, this advantage is extremely useful for generating probes that bind to glycosaminoglycans. Thus, phage display technology is increasingly important for studying the functions of glycosaminoglycans (47)(48)(49)(50)(51)(52). The generation of type-specific anti-HS antibodies using phage display technology was initially applied by van Kuppevelt et al (53) for investigating HS heterogeneity in the kidney.…”
Section: Discussionmentioning
confidence: 99%